2014
DOI: 10.2138/am.2014.4782
|View full text |Cite
|
Sign up to set email alerts
|

Volatile abundances of coexisting merrillite and apatite in the martian meteorite Shergotty: Implications for merrillite in hydrous magmas

Abstract: Whitlockite and merrillite are two Ca-phosphate minerals found in terrestrial and planetary igneous rocks, sometimes coexisting with apatite. Whitlockite has essential structural hydrogen, and merrillite is devoid of hydrogen. Whitlockite components have yet to be discovered in samples of extraterrestrial merrillite, despite evidence for whitlockite-merrillite solid solution in terrestrial systems. The observation of merrillite in meteoritic and lunar samples has led many to conclude that the magmas from which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 61 publications
5
91
1
Order By: Relevance
“…McCubbin et al [12,58] and Vander Kaaden et al [59] define the order of preference as follows: F >> Cl > OH. Hence, F plays an important role in stabilizing magmatic apatite, and during degassing, apatite compositions evolve towards the F-rich member.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…McCubbin et al [12,58] and Vander Kaaden et al [59] define the order of preference as follows: F >> Cl > OH. Hence, F plays an important role in stabilizing magmatic apatite, and during degassing, apatite compositions evolve towards the F-rich member.…”
Section: Discussionmentioning
confidence: 99%
“…Some grains contain Cl amounts at the limit of detection (<50 ppm). Trace abundances of halogens in extra-terrestrial merrillites have been reported [6,12,50].…”
Section: Phosphate Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occasionally, other types of natural CaPO 4 are found as minerals, for example clinohydroxylapatite (Chakhmouradian and Medici 2006), staffelite (synonyms: staffelit, staffelita) belonging to carbonate-rich fluorapatites (chemical formula: Ca 5 [(F,O)(PO 4 ,CO 3 ) 3 ]) (Mason et al 2009; http:// www.mindat.org/gallery.php?min=9293) and DCPD (Klein 1901;Kaflak-Hachulska et al 2000). Furthermore, CaPO 4 were found in meteoric stones (Merrill 1917;McCubbin and Nekvasil 2008;McCubbin et al 2014). The world deposits of natural CaPO 4 are estimated to exceed 150 billion tons; from which approximately 85 % belong to phosphorites and the remaining *15 % belong to apatites (Cook et al 2005).…”
Section: Geological and Biological Occurrencesmentioning
confidence: 99%